Compositional skills error analysis: The case of the university environmental engineering first-year students - Isabelita C. Bodbod; Ronelo G. Cablinda; Arnel S. Travero (Institute of Advanced Engineering and Science, 2023)
The compositional skills are analyzed to determine whether college students have improved their writing ability after the two years additional in the senior high school curriculum. This study examines the errors committed by first-year engineering students. There were 90 student respondents written outputs collected and subjected to Grammarly software. The researchers analyzed the data using the Scheffe test, comparing the difference between clarity, engagement, and delivery. Analysis of Variance (ANOVA) was employed to test whether there is a significant difference among other variables. Findings revealed that clarity is the most common error committed by the student-respondents. The errors committed between male and female respondents do not show a difference. The K-12 graduates’ compositional errors do not differ significantly from that in the Alternative Learning System (ALS) passers or the old basic education curriculum graduates. It is in delivery that students vary. This finding implies that college students' compositional skills still need strengthening. Instructors are encouraged to provide comprehensive activities and writing exercises to both genders, regardless of their curriculum. It is recommended that University language instructors identify specific interventions to help students struggling with writing. Therefore, providing enough written opportunities and practices is vital to make college students enhance their compositional skills.